Curriculum Management at SMP Negeri 1 Biatan: Planning, Implementation, Supervision, and Evaluation - Baco, Asmar; Haeruddin, Haeruddin; Akhmad, Akhmad (Holistic Science, 2025)
Curriculum management plays a strategic role in ensuring the achievement of quality education goals, especially in remote areas like Biatan. This study aims to describe and analyze curriculum management at SMP Negeri 1 Biatan, encompassing planning, implementation, supervision, and evaluation. This study employed a descriptive qualitative approach with a case study method. Data were collected through interviews, observation, and documentation, then analyzed using Miles and Huberman's interactive analysis techniques. The results indicate that curriculum planning is carried out collaboratively and based on local data, while its implementation refers to the principles of the Independent Curriculum with the application of differentiated learning. Supervision is carried out through regular academic and managerial supervision, and evaluation is carried out to measure program effectiveness and learning outcomes, which are followed up with continuous curriculum improvements. Despite facing limited resources and teacher readiness, SMP Negeri 1 Biatan demonstrates a strong commitment to building an adaptive curriculum management system oriented towards quality improvement. This research makes an important contribution to the development of curriculum management in educational units in remote areas.